SISTEM SAPAAN KEKERABATAN SUKU SASAK: KAJIAN LINGUISTIK KEBUDAYAAN - Haerudin Haerudin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This study investigates kinship greeting in Sasaknese.  The study used ethnolinguistic approach that described aspects of relation between language and culture to maintain cultural practices and social structure of a society.  The study revealed: (1) the Sasak kinship greetings had relation to the kinship structure, having hierarchical boundaries of four generations above one’s family group chart and three generations below one’s family group chart, and are related to users’ age; (2) the custom greetings have social and cultural functions; (3) the existing condition of the use of the kinship greetings is undergoing a shifting in some areas on Lombok Island as a result of modernization. The shifting is merely occurred on the greetingforms; whereas others, which are related to the kinship structure and the users’ age, remain as the characteristic of Sasak tribe; (4) by constantly using the kinship greetings, Sasak people, have participated in preserving the cultural riches; that is the local language. This effort constitutes one of the strategies in preventing language extinction as the cultural heritage of the nation.